Diffusivities and atomic mobilities in BCC Ti-Rich Ti–V–Cr ternary alloys. (March 2022) - Gao, Ning; Bai, Weimin; Hu, Qi; Liu, Libin; Zhang, Ligang
Abstract: In this work, we investigate ternary diffusion behaviors in BCC Ti–rich Ti–V–Cr alloys at 1373 K and 1473 K using the diffusion couple technique. We extract the inter-diffusion coefficients by the Whittle-Green method and obtain the impurity diffusion coefficients using the Hall method. Based on a thermodynamic description and validated binary mobility parameters, we evaluate the ternary diffusion coefficients and optimize the atomic mobility parameters of the Ti–V–Cr ternary alloy system in the DICTRA diffusion Module of Thermo-Calc software. Finally, we simulate the composition profiles and diffusion paths using our optimized atomic mobility parameters and find agreement between our simulated and experimentally observed results, providing evidence of the accuracy of our mobility parameters.